Becoming Deleuzian?. Issue 4 (November 2019) - Perniola, Mario
Abstract : Mario Perniola finds more than one cause in common with Deleuze, establishing a link between some aspects of Deleuze's theories and his own education, oriental philosophy, the situationists, but mostly Surrealism and Stoicism, two philosophical attitudes sharing the awareness that the threshold between actuality and virtuality is shifting and in constant transformation. The core element of the essay is notably the notion of becoming, to be taken strictly in relation to the notions of assemblage and plane of consistency. Together they account for one and the same moment, a disposition of elements, which is not stable but in constant movement.